The Influence of Organizational Culture and Non-Physical Work Environment on Performance Pegawai pada Dinas Pariwisata, Pemuda dan Olahraga Kabupaten Karanganyar - Indar Khoiriyah; Syarifuddin Syarifuddin (Universitas Pamulang, 2022)
The Karanganyar Regency Tourism, Youth and Sports Office is one of the Regional Apparatuses that carries out government affairs in the tourism, youth and sports fields in Karanganyar Regency. Human resources are one of the most important factors in an organization, so human resources must be managed properly and correctly in order to increase effectiveness in the company or organization. Many factors influence this, such as organizational culture, non-physical work environment, and employee performance. This study aims to determine the influence of organizational culture and non-physical work environment on employee performance at Disparpora Karanganyar Regency. The method used is a quantitative method and a descriptive type of research, and takes a sample of 34 respondents from all employees of the Karanganyar Regency Disparpora. This study uses multiple linear regression analysis with SPSS version 26 program and descriptive analysis. The results of this study are descriptive analysis shows that the variables of organizational culture, non-physical work environment, and employee performance are in the very good category. Meanwhile, the multiple linear regression analysis test shows that there is a significant influence of the organizational culture and non-physical work environment variables either partially or simultaneously.